Immunohistochemical analysis of the arterial supply and mast cells of the trigeminal ganglion - Mirčić, Aleksandar Lj.; Maliković, Aleksandar B.; Štimec, Bojan V.; Milosavljević, Aleksandra G.; Ćetković, Dejan B.; Dožić, Aleksandra M.; Boljanović, Jelena S.; Đoković, Jelena Đ.; Ćetković, Mila V. (Archives of Biological Sciences, 2021)
Paper description: Microvessels in the trigeminal ganglion and the number of mast cells within the ganglion and the periganglionic area, which could influence sensory fibers in a specific portion of the ganglion, have not been examined. Using immunohistochemical staining we observed intraganglionic microvessels and mast cells within the ganglion and in the periganglionic area, and a uniformly arranged intraganglionic network of blood vessels within the trigeminal ganglion. The number of intraganglionic mast cells is small and uniformly arranged, intradural and periganglionic mast cells are more numerous, which points to the potential influence on headache development. Abstract: The aim of this study was to quantify the distribution of microvessels and mast cells in all three parts of the trigeminal ganglion (TG). Statistical analyses were applied to investigate possible micromorphological regional differences in their density. Five serially sectioned human TGs were prepared for CD34 and mast cell tryptase immunostaining. The following quantifications were performed in microscopic fields of three parts of the TG: microvessel density (MVD), mast cell density (MCD) and ganglionic cell count. The density of CD34-positive microvessels was not significantly different in any of the three observed parts of the TG. The distribution of neurons showed no significant statistical difference in three parts of the TG. There was no difference in the density of tryptase-positive mast cells within the TG, but there was an abundant presence of mast cells in the periganglionic dural and subdural tissues, a finding hitherto not reported. We can say that there is a homogenous vascular pattern within the TG which excludes local predominance in pathogenesis of trigeminal neuralgia. Second, and more important, the finding of peri-trigeminal mast cells indicates their important role in migraine pain and confirms their degranulation as the main therapeutic goal for this condition.